Deregulation of miRNAs-cMYC circuits is a key event in refractory celiac disease type-2 lymphomagenesis. Issue 10 (22nd May 2020) - Vaira, Valentina; Gaudioso, Gabriella; Laginestra, Maria Antonella; Terrasi, Andrea; Agostinelli, Claudio; Bosari, Silvano; Di Sabatino, Antonio; Vanoli, Alessandro; Paulli, Marco; Ferrero, Stefano; Roncoroni, Leda; Lombardo, Vincenza; et al.
Abstract: A percentage of celiac disease (CD) patients develop refractory type-2 disease (RCD2), a condition associated with increased risk of enteropathy-associated T-cell-lymphoma (EATL) and without therapeutic option. Therefore, we profiled the miRNome in series of peripheral T-cell lymphomas (PTCLs), CD, RCD1 or 2 and in the murine interleukin-15 (IL15)-transgenic (TG) model of RCD. The transcriptome was analyzed in 18 intestinal T-cell lymphomas (ITLs). Bioinformatics pipelines provided significant microRNA (miRNA) lists and predicted targets that were confirmed in a second set of patients. Our data show that ITLs have a unique miRNA profile with respect to other PTCLs. The c-MYC regulated miR-17/92 cluster distinguishes monomorphic epitheliotropic ITL (MEITL) from EATL and prognosticates EATL outcome. These miRNAs are decreased in IL15-TG mice upon Janus kinase (JAK) inhibition. The random forest algorithm identified a signature of 38 classifier miRNAs, among which, the miR-200 and miR-192/215 families were progressively lost in RCD2 and ITL-CD, whereas miR-17/92 and C19MC miRNAs were up-regulated. Accordingly, SMAD3, MDM2, c-Myc and activated-STAT3 were increased in RCD2 and EATL tissues while JAK inhibition in IL15-TG mice restored their levels to baseline. Our data suggest that miRNAs circuit supports activation of STAT3 and c-Myc oncogenic signaling in RCD2, thus contributing to lymphomagenesis. This novel understanding might pave the way to personalized medicine approaches for RCD and EATL.